Create and Counter-Narrate Research Methodologies and Non-hegemonic Creation Processes in Visual Arts at the Federal University of Sergipe and Federal University of Bahia (Revista Apotheke, 2024)
This article arises from the exchange of experiences between two professors of the college degree at the Federal University of Bahia and Federal University of Sergipe. Debates different pedagogical practices in the teaching of the visual arts that contemplate anti-colonial and intersectional counter-narratives, considering several markers of difference, not dissociating the different subordination axes, as race, class and sexuality to think about academic research and creation processes in Visual Arts. This text reflects how the practices and readings of the writings by Grada Kilomba, bell hooks, Nêgo Bispo, Luiz Antônio Simas, Luiz Rufino, Kimberlé Crenshaw and Patrícia Hill Collins influence the construction of methodologies for reflection, discussion and production crossed by themes understood as dissident. In this way, they propose a critical look at the curricular components Research Methodology in Visual Arts and Ceramic I and II.
Keywords: visual arts research; non-hegemonic teaching; research methodology; rceation processes